A numerical study of water entry of asymmetric wedges using a CIP-based model. (15th January 2018) - Hu, Zijun; Zhao, Xizeng; Li, Mengyu; Fang, Zhouhua; Sun, Zhilin
Abstract: The two-dimensional water entry of wedges with different inclination angles is numerically investigated using a constrained interpolation profile (CIP)-based model, which is developed on the ground of a fixed Cartesian grid and governed by the Navier-Stokes (N-S) equations. A high-order finite difference method is employed as the flow solver, where the CIP method is used to discretize the convective term. The tangent of hyperbola for interface capturing/slope weighting (THINC/SW) is adopted to capture the free surface/interface, and an immersed boundary method is applied to simulate the motion of bodies. The present numerical model involving symmetric water entry is verified in comparison with the previous numerical and experimental results in the literature. The results of the asymmetric water entry are provided in terms of the penetration depth, velocity, pile-up coefficients, impact force of wedges, and velocity and pressure distributions of fluid. Considerable attention is paid into the effects of deadrise and inclination angles. It is found that the presence of the inclination angle significantly influences both the velocity and pressure field, and further regulates the penetration depth, velocity, pile-up coefficients, and impact force on the wedge. Specifically, wedges entering into the water with small deadrise angles are found to be more sensitive to the inclination angle than those with large deadrise angle. Highlights: Water entry of asymmetric wedges are numerically studied using an in-house code. The model is validated against experimental data with good agreement. The effects of deadrise and inclination angles of the wedge are analyzed. The locations of the maximum values of flow velocity and pressure are studied.